(3LhgQI GdCUhd hJPcQI GdaMhds - (3CHh GdMSf CMeO Hf eMeO Hf GdMSf Hf eMeO GdQUGU,J (B565 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hdi GdMeO HeG GaGV ef SLGd GdEMSGf s
(3BNQgG (B:s
(3hESJjaGA Pdc hGdQO Ydi GdbGFdjf Hg ehVhYg CUhd GdOjf , hgPG Mjf CJjfG Ydi GdaQGZ ef GdcJGH (B,(3MSHfG Gddg hfYe Gdhcjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3Ydi MhGTjgG JYdjbGJ hJUMjMGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ GdZQHjI (B((3abg (B39) s
Keywords: (3Gdabg GdESdGejs